PEDAGOGICAL CONTROL OF THE TRAINING MANAGEMENT PROCESS FOR 11–12-YEAR-OLD FOOTBALLERS - Temur Palvaniyazov Ametjanovich; Aybek Aytimov Aymurat uli (Proximus Journal Publishing, 2024)
to study the movement techniques of 10-12-year-old players on the field, to scientifically justify the fact that coaches can distribute loads in training sessions based on the distance they cover. Also, the importance of pedagogical analysis in football: theory and practice is studied. Currently, in order to successfully manage the training process of the football team, the coach must have objective information about the players in the team, that is, about their mental and health, including the functional parts of the physical exercises given to young players. One of the most important aspects is to correctly evaluate the level of technical and tactical skills of players, in order to train them in the future to become highly skilled players. The issue presented in this article is of great importance.
Keywords: Technical and tactical training; step length; step rhythm; distance